Combatting illicit trade on the EU border : a comparative perspective - Nowak, Celina (Springer, 2021)
This open access book provides the first-ever comparative study on criminal policy concerning the illicit trade of tobacco, conducted among four comparatively new EU Member States (Lithuania, Poland, Slovakia and Romania) and two "old" EU countries (Germany and Italy). The book addresses the national legal frameworks, current criminological situation regarding illicit trade of tobacco, and the practical challenges faced by national law enforcement authorities in the countries examined. It also considers the international framework, and concludes with a horizontal report. The objective of the book is to highlight legislative and practical challenges in the fight against illegal tobacco products at the national and transnational level, and to formulate recommendations for overcoming them more effectively in Europe.-- Provided by publisher
Keywords: Commercial law -- European Union countries.; Smuggling -- Law and legislation -- European Union countries.; Conflict of laws.; International law.; Droit international privé.; Smuggling -- Law and legislation; Commercial law; Conflict of laws; International law; European Union countries; European Economic Law; Private International Law, International & Foreign Law, Comparative Law; International Economic Law, Trade Law; Private International Law, International and Foreign Law, Comparative Law; Criminal law; Criminal policy; Comparative criminal law; Illicit tobacco trade; Tobacco regulation; Open access; Public international law: economic & trade; Comparative law; Electronic books.